Lymphoplasmacytic sclerosing pancreatitis - Chetty, R; Vajpeyi, R (2005)
Lymphoplasmacytic sclerosing pancreatitis has been reported in the literature under a variety of names. It is a characteristic lesion of auto-immune origin occurring most often in middle-aged and elderly males. It is associated with several other auto-immune diseases, particularly primary sclerosing cholangitis and Sjögren's syndrome. The most common presenting symptoms are jaundice and abdominal pain. Both clinical and radiological examination favour carcinoma of the pancreas. The characteristic ductulocentric lymphoplasmacytic inflammatory infiltrate with associated sclerosis involves the pancreas and the biliary tract, with varying severity. Loss of exocrine pancreatic tissue with preservation of the islets of Langerhans is noted. Phlebitis and extension of the inflammation around nerves and into peripancreatic fibrofatty tissue are also common features. The sclerosis results in narrowing of the main and interlobular pancreatic ducts, common bile duct and even cystic duct. Importantly, fat necrosis, pseudocyst formation, duct dilatation, calcification and other known causes of chronic pancreatitis are absent. Treatment is a combination of surgery and steroid therapy. © 2004 Elsevier Ltd. All rights reserved.